THE FORMATION OF THE READINESS OF A FUTURE ENGINEER FOR THE MANAGEMENT OF PRODUCTION AND TECHNOLOGICAL RISKS - Isabella D. Belonovskaya; Elena M. Ezerskaya (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In the article the readiness for risk management is treated as an actual component of the engineering competence which determines the opportunity and productivity of the objective, conscious and competent activity which are in competence of the bachelor by the establishment of the character of production and technological risks and the solution of problems of localization, compensation and elimination of possible negative consequences of the activity of manufacturing enterprises. In the course of its formation, the maintenance of engineering education corresponds to the requirements of professional standards, innovative productions and risk analysis in industries; the practice of engineering education joins the methods of modeling and prototyping which are learnt by the students in the interdisciplinary educational and independent work, research activity and work practice during the interaction of students, teachers and employers.